Efektivitas Penggunaan Essay Pada Evaluasi Pembelajaran Matematika Kelas IV Di MIN 2 Kota Palangka Raya - Febriani Ekayanti; Istiyati Mahmudah (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2024)
In the midst of the dynamics of Indonesian education, learning evaluation plays a very important role. Evaluations not only measure student achievement, but also identify effective teaching methods. The success of teaching is not only seen from the learning outcomes achieved by students, but also in terms of the process. To determine the success of learning objectives, an educator needs to carry out learning evaluations. In conducting evaluations, teachers are given the freedom to determine their own form of evaluation used. There are many types of evaluation tools in learning such as multiple choice, essays, matching and many more. The aim of this evaluation is to make it easier for a teacher to carry out a task or achieve a goal effectively and efficiently. This research aims to determine the effectiveness of using essays as a learning evaluation. This research uses descriptive qualitative research. The technique used in data collection was an interview with one of the 4th grade teachers at MIN 2 Palangka Raya City. The research results show that the use of essays in mathematics subjects in grade 4 is more effective than using other forms of evaluation. Because, students can be invited to think more critically in working on the questions given, so that students can solve them well.